The Influence of Learning Orientation, Customer Orientation and Product Knowledge of Salesforce Car Performance at Padang City Dealers - Nadia Sawitri; Thamrin Thamrin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The competition in the automotive industry is getting fiercer, making car dealers keep trying to improve the performance of their salespeople so that they can achieve sales targets. This study aims to see the impact of three things, namely learning orientation, customer orientation behavior, and product knowledge on the performance of salespeople at car dealers in Padang City. This study was based on the differences between targets and sales results that were still far away in some showrooms, which showed internal factors affecting salespeople's effectiveness. This study used a quantitative approach by surveying 96 salespeople who had worked for at least five years. The data was collected through questionnaires with a Likert scale, then analyzed using multiple linear regression via SPSS software. Research results show that all three variables affect sales performance positively and significantly. These findings emphasize the importance of learning orientation, understanding of customer needs, and good product knowledge in improving sales performance. The hope of this research is to contribute theoretically to the development of sales management as well as to assist automotive dealers in improving the quality and strategy of their sales teams.